Investigation of the status and the prospect of fuel pellet production and utilisation toward net zero emissions by 2050 in Vietnam - Do Xuan Truong (Vietnam Journal of Science, Technology and Engineering)
The Vietnamese government has committed strongly to reducing greenhouse gas emissions to zero by 2050 at the United Nations Climate Change Conference in Glasgow (COP26). Vietnam possesses significant potential to develop renewable energy from wood biomass and agricultural residues. This study comprehensively evaluates the status and potential of fuel pellet production and utilisation in Vietnam. Factors affecting fuel pellet production were evaluated. Vietnam’s total wood pellet output is approximately 5 million tonnes per year. Raw materials are mainly derived from residues of plantation forests (90%) and the wood processing industry (10%). Vietnam’s wood pellet production potential could increase two to three times due to the extensive plantation forest resource of nearly 5 million hectares. Currently, Vietnam does not utilise any wood pellets or wood chips as fuel to produce electricity domestically. The Vietnamese government is strongly committed to achieving net- zero emissions by 2050 and has implemented numerous policies and mechanisms to encourage the development of renewable energy. Owing to the vast potential of biomass from both forestry and agricultural residues, the export of wood fuel, such as wood pellets and wood chips, is expected to continue increasing in the future due to rising global demand.